The beguniaceae of colombia (1946)
Begonia (§ Ruizopavonia) Dugandiana / Begonia (§ Ruizopavonia) alnifolia / Begonia (§ Pritzelia) glabra / Begonia (§ Begoniastrum) guaduensis / Begonia (§ Begoniastrum) Barrigae / Begonia (§ Meionanthera) Holtonis / Begonia (§ Lepsia) microphylla / Begonia (§ Lepsia) foliosa  / Begoniella / Begoniella Whitei / Begoniella libera / Begoniella Kalbreyeri / Begoniella angustifolia.